Cognitive Stimulation for Apathy in Probable Early-Stage Alzheimer's - Linda L. Buettner; Suzanne Fitzsimmons; Serdar Atav; Kaycee Sink (Journal of Aging Research)
We studied changes in apathy among 77 community-dwelling older persons with mild memory loss in a randomized clinical trial comparing two nonpharmacological interventions over four weeks. The study used a pre-post design with randomization by site to avoid contamination and diffusion of effect. Interventions were offered twice weekly after baseline evaluations were completed. The treatment group received classroom style mentally stimulating activities (MSAs) while the control group received a structured early-stage social support (SS) group. The results showed that the MSA group had significantly lower levels of apathy (P<.001) and significantly lower symptoms of depression (P<.001). While both groups improved on quality of life, the MSA group was significantly better (P=.02) than the SS group. Executive function was not significantly different for the two groups at four weeks, but general cognition improved for the MSA group and declined slightly for the SS group which produced a significant posttest difference (P<.001). Recruitment and retention of SS group members was difficult in this project, especially in senior center locations, while this was not the case for the MSA group. The examination of the data at this four-week time point shows promising results that the MSA intervention may provide a much needed method of reducing apathy and depressive symptoms, while motivating participation and increasing quality of life.